2002
DOI: 10.1046/j.1523-1747.2002.01615.x
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic Acid, a n-3 Polyunsaturated Fatty Acid Differentially Modulates TNF-α, IL-1α, IL-6 and PGE2 Expression in UVB-Irradiated Human Keratinocytes

Abstract: In response to UVB-irradiation keratinocytes release a variety of cytokines and prostaglandins, including tumor necrosis factor alpha (TNF-alpha), interleukin 1alpha (IL-1alpha), interleukin 6 (IL-6), and prostaglandin E2 (PGE2). n-3 Polyunsaturated fatty acids (PUFA), mainly present in fish oil, can modulate cytokine synthesis, as predominantly studied in macrophages. In order to investigate the immune modulating actions of n-3 PUFA on the UVB response in human skin, we investigated the effect of eicosapentae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 48 publications
7
51
0
3
Order By: Relevance
“…PGE 2 is more mitogenic and proinflammatory than PGE 3 . It has been reported that fish oils, rich in -3 PUFAs, possess anti-inflammatory properties in UV-exposed skin (15). Recently, EPA and DHA were reported to reduce basal and UV-induced interleukin-8 secretion by keratinocytes and fibroblasts (16).…”
mentioning
confidence: 99%
“…PGE 2 is more mitogenic and proinflammatory than PGE 3 . It has been reported that fish oils, rich in -3 PUFAs, possess anti-inflammatory properties in UV-exposed skin (15). Recently, EPA and DHA were reported to reduce basal and UV-induced interleukin-8 secretion by keratinocytes and fibroblasts (16).…”
mentioning
confidence: 99%
“…Supplementation with omega-3 fatty acids also results in the generation of three-series prostanoids and reduces release of PGE2 [20]. The omega-3 fatty acids compete with AA for their phospholipase-mediated release from membranes [21] and for metabolism of the free fatty acids by cyclo-oxygenase and lipoxygenase [22].…”
Section: Discussionmentioning
confidence: 99%
“…DHA and EPA enhance TNF-α and IL-6 secretion in macrophages [15][16][17], and dietary fish oil supplementation increases serum TNF-α concentration in response to endotoxin challenges [15]; thus, n-3 PUFAs are regarded as pro-inflammatory factors. Treatment with n-3 PUFAs also increases TNF-α, IL1a, and IL-6 expression in adipocytes, keratinocytes, splenocytes, and hepatocytes [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 91%